Evaluating, Improving, and Appreciating Peer Review at IJTMB - Kennedy, LMT, BCTMB, DrPH, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2021)
Peer review is a mainstay of scientific publishing and, while peer reviewers and scientists report satisfaction with the process, peer review has not been without criticism. Within this editorial, the peer review process at the IJTMB is defined and explained. Further, seven steps are identified by the editors as a way to improve efficiency of the peer review and publication process. Those seven steps are: 1) Ask authors to submit possible reviewers; 2) Ask reviewers to update profiles; 3) Ask reviewers to “refer a friend”; 4) Thank reviewers regularly; 5) Ask published authors to review for the Journal; 6) Reduce the length of time to accept peer review invitation; and 7) Reduce requested time to complete peer review. We believe these small requests and changes can have a big effect on the quality of reviews and speed in which manuscripts are published. This manuscript will present instructions for completing peer review profiles. Finally, we more formally recognize and thank peer reviewers from 2018–2020.